Digital Game-Based Learning Innovation in Higher Education: Bibliometric Analysis and Recommendations for Future Research - Rohmani; I Wayan Distrik; Herpratiwi; Dina Maulina (Indonesian Journal of Educational Research and Review)
Rapid technological developments have made digital games an innovative and effective tool in improving the quality of learning, especially for students around the world. Although the use of digital games in higher education is increasing, in-depth research on this topic is still limited. Therefore, this study aims to analyze the use of digital games in the context of higher education and to fill the existing knowledge gap. The method used is bibliometric analysis, data sourced from the Scopus.com database, which is then analyzed using Zotero and VOSviewer software. Bibliometric analysis is used to identify trends, assess quality, and track developments. Data searches on the Scopus.com database produced 146 documents, 118 of which were selected based on predetermined criteria. The results of the analysis show that after 2015, there has been a significant increase in publications on digital games in the context of higher education, most of which were written by researchers from the United States, with 57 papers contributing 58.6% of citations. The journals "Internet and Higher Education" and "Computers in Human Behavior" emerged as the main sources with the highest number of citations, indicating high quality and scientific impact. Keyword analysis revealed that topics such as game-based learning, collaboration, and digital literacy are emerging research trends. The conclusions of this study underscore the significant potential of digital games as effective pedagogical tools and provide a foundation for further research in this area.